Reputation: 635
I want to implement the following function f(x,y)
in Prolog
f(x,y) = a*x+b*y
where a = 1 if x > 0; a = -1 if x < 0; a = 0 if x = 0
and b = -1 if y > 0; b = 1 if y < 0; b = 0 if y = 0
For example,
f(2,-1) = 1*2 + 1*(-1) = 1
f(-2,-1) = (-1)*(-2) + (-1)*1 = 1
f(0,0) = 0*0 + 0*0 = 0
Any one can help?
Upvotes: 2
Views: 401
Reputation: 74197
Shouldn't be much more complicated than this one-liner:
f(X,Y,Z) :- Z is sign(X)*X + -sign(Y)*Y
Upvotes: 0
Reputation: 18726
How about using the following formulation?
f(X,Y,Result) :-
Result is abs(X) - abs(Y).
Let's run some queries:
?- f(0,0,0).
true.
?- f(-2,-1,1).
true.
?- f(2,-1,1).
true.
Upvotes: 1
Reputation: 4797
(Assuming you have a typo when defining y, y>0 not y>=0.) You need to define a relation between the input vars and the result of the function. Prolog can then answer yes/true with substitutions or no/false.
f(X,Y,Answer):-
a_is(X,A),
b_is(Y,B),
Answer is A*X+B*Y.
a_is(X,1):-
X>0.
a_is(X,-1):-
X<0.
a_is(0,0).
b_is(Y,1):-
Y<0.
b_is(Y,-1):-
Y>0.
b_is(0,0).
Example:
?-f(2,-1,Answer).
Answer =1;
false.
Upvotes: 0